ANALYSIS OF ASSOCIATION BETWEEN THE POLYMORPHIC VARIANTS OF THE TLR2 (RS5743708) AND TLR4 (RS4986790, RS4986791) GENES WITH THE HEALTH STATUS OF APPARENTLY HEALTHY INDIVIDUALS - O.V. Izmailova (Проблеми екології та медицини)
Тhe study of single-nucleotide polymorphisms of Toll-like receptors has an important applied and theoretical value for revealing the mechanisms in formation of immunity features and its correction. The aim of the research was to study the available frequency of polymorphic variants of the TLR2 gene (rs5743708) and 896A/G (rs4986790), 1196C/T (rs4986791) of the TLR4 gene, and to assess the association with the health status of apparently healthy individuals. Materials and methods: the study involved 114 Caucasian individuals living in Poltava or Poltava oblast for a minimum of 2 years, who underwent the collection of anamnestic data, as well as the data of objective and clinical examinations. The polymorphic sites of the TLR2 (rs5743708) and TLR4 genes (rs4986790, rs4986791) were determined by polymerase chain reaction (PCR) followed by analysis of the restriction fragments length of the PCR products. The results of distribution of polymorphic variants 2258G/A in the genotypes of the TLR2 gene (rs5743708), 896A/G of the TLR4 gene (rs4986790), and 1196C/T of the TLR4 gene (rs4986791) corresponded to the theoretically expected ones at the Hardy-Weinberg equilibrium (χ2 = 0.02, р = 0.99; χ2 = 0.29, р = 0.86; χ2 = 1.46, р = 0.48, respectively). When comparing the presence of individual clinical manifestations that were detected during the interviewing, with the presence of polymorphic alleles in the genotype, a reliable relationship was established between the presence of the A allele in the polymorphic version of the TLR2 gene (rs5743708) in the genotype with rheumatism (p = 0.05), pyelonephritis (p = 0.05) and a bad habit of smoking (p = 0.04).